2015
DOI: 10.1002/adsc.201500700
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Formation of N‐Heteroarenes from Nitroarenes using Molybdenum Hexacarbonyl as the Source of Carbon Monoxide

Abstract: Thed evelopment of am ethod that employs at wo-chamber reaction vessela nd usesm olybdenum hexacarbonyl [Mo(CO) 6 ]a st he carbon monoxide (CO) source for the palladium-catalyzed transformation of nitroarenes into indoles or imidazoles is reported. Thes cope andl imitations of our method are illustrated with 23 examples.E xperiments that indicatet he mechanism of the C À H bond amination reactiont ob es tepwisea re also reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 92 publications
0
34
0
Order By: Relevance
“…As a comparison, if the previously investigated protocol based on n ‐butyl formate was applied, lower yields were achieved (see compounds 2 a , 2 h , 2 n , 2 q , and 2 t ), which thus confirmed the effectiveness of phenyl formate as a CO source . Notably, in several cases the achieved yields were higher than those previously reported in the literature by using pressurized CO. For example, the best yields obtained in the cases of compounds 2 a , 2 h , 2 e , and 2 q were 83, 63, 87, and 55 %, respectively. This fact clearly demonstrates that our protocol is a virtuous alternative to those based on the use of pressurized CO.…”
Section: Methodsmentioning
confidence: 98%
“…As a comparison, if the previously investigated protocol based on n ‐butyl formate was applied, lower yields were achieved (see compounds 2 a , 2 h , 2 n , 2 q , and 2 t ), which thus confirmed the effectiveness of phenyl formate as a CO source . Notably, in several cases the achieved yields were higher than those previously reported in the literature by using pressurized CO. For example, the best yields obtained in the cases of compounds 2 a , 2 h , 2 e , and 2 q were 83, 63, 87, and 55 %, respectively. This fact clearly demonstrates that our protocol is a virtuous alternative to those based on the use of pressurized CO.…”
Section: Methodsmentioning
confidence: 98%
“…[22] Thesecond role of palladacycle 7 is to trigger the CÀHb ond activation of the substrate (1a)t op roduce biscyclometallated 10. Alternatively,t he amide could be formed from the reaction of palladacycle 10 with arylisocyanate, [4,5] which could be formed from the [Mo(CO) 6 ]-mediated reduction of the nitroarene, [17] or from the reaction of aniline or Nhydroxy-aniline with acyl-Pd species 11.T he lack of amide formation when isocyanate,a niline,o rN-hydroxyaniline are used as the nitrogen source,h owever, strongly suggests that bond formation does not occur through these two potential pathways. [24] Reduction of the NÀObond in 14 by molybdenum or palladium then produces the product amide.This reduction could occur before or after dissociation of the palladacycle catalyst.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…We have shown that Pd-catalyzed intermolecular C À H bond aminocarbonylation of 2-aryl-or 2-heteroarylpyridines can be achieved using nitroarenes as the nitrogen source and [Mo(CO) 6 ]a st he carbonyl source.O ur mechanistic studies revealed that the active catalyst is apalladacycle,which serves to both reduce the nitroarene to an itrosoarene as well as activate the aryl C À Hb ond. Our future studies will build on these results by exploring the reactivity of palladacycles towards nitroarenes to trigger intermolecular CÀNb ondforming reactions to rapidly and efficiently build complexity of simple heteroarenes.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 2 more Smart Citations